Action-Specific Perception in Internal and External Attention Focus Conditions - Borhanaldin Ghari; Hasan Mohammadzadeh; Jalal Dehghanizadeh (University of Tehran, 2017)
The aim of this study was to investigate the relationship between performance and the perception of size of target under internal and external attention focus conditions as well as the relationship between the initial perception of the size of target and performance. 70 male students (mean age of 21±1.6 years) voluntarily participated in this study. They were randomly assigned to internal and external attention focus based on the type of attentional instruction. Subjects performed dart throwing task in 20 trials. The target size estimation test was performed before the trials, after the last trial and after the first successful trail. Pearson correlation coefficient was used for data analysis. The results showed a significant and positive relationship between the performance and perception of target size in external focus group. But in internal focus group, a significant relationship between performance and perception of the size of the target was not observed. Also, there was no significant relationship between the initial perception and performance in both groups. It is suggested that the focus of attention can be a mediating factor for action-specific perception phenomenon.